In vivo characterization of ischemic small intestine using bioimpedance measurements. (25th January 2016) - Strand-Amundsen, R J; Tronstad, C; Kalvøy, H; Gundersen, Y; Krohn, C D; Aasen, A O; Holhjem, L; Reims, H M; Martinsen, Ø G; Høgetveit, J O; Ruud, T E; Tønnessen, T I
Abstract: The standard clinical method for the assessment of viability in ischemic small intestine is still visual inspection and palpation. This method is non-specific and unreliable, and requires a high level of clinical experience. Consequently, viable tissue might be removed, or irreversibly damaged tissue might be left in the body, which may both slow down patient recovery. Impedance spectroscopy has been used to measure changes in electrical parameters during ischemia in various tissues. The physical changes in the tissue at the cellular and structural levels after the onset of ischemia lead to time-variant changes in the electrical properties. We aimed to investigate the use of bioimpedance measurement to assess if the tissue is ischemic, and to assess the ischemic time duration. Measurements were performed on pigs ( n   =  7) using a novel two-electrode setup, with a Solartron 1260/1294 impedance gain-phase analyser. After induction of anaesthesia, an ischemic model with warm, full mesenteric arterial and venous occlusion on 30 cm of the jejunum was implemented. Electrodes were placed on the serosal surface of the ischemic jejunum, applying a constant voltage, and measuring the resulting electrical admittance. As a control, measurements were done on a fully perfused part of the jejunum in the same porcine model. The changes in tan δ (dielectric parameter), measured within a 6 h period of warm, full mesenteric occlusion ischemia in seven pigs, correlates with the onset and duration of ischemia. Tan δ measured in the ischemic part of the jejunum differed significantly from the control tissue, allowing us to determine if the tissue was ischemic or not ( P   <  0.0001, F   =  (1, 75.13) 188.19). We also found that we could use tan δ to predict ischemic duration. This opens up the possibility of real-time monitoring and assessment of the presence and duration of small intestinal ischemia.